1998
DOI: 10.1046/j.1365-2567.1998.00480.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of cytotoxic alloreactivity by human allogeneic mononuclear cells: evidence for veto function of CD2+ cells

Abstract: In animal models of organ transplantation, infusion of donor-derived leucocytes or bone marrow cells can support tolerance induction. To date, little is known about the suppressive effects of human allogeneic mononuclear cells on alloreactivity in the human system. To study this, mixed leucocyte cultures (MLC) were incubated in the presence and absence of viable allogeneic mononuclear cells (MNC) (modulator cells) of stimulator/donor origin, and the cytotoxic and proliferative potential of the resulting effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The early immunomodulation achieved by expression of FasL protein on the surface of HSPC in concert with the insensitivity of these cells to Fas‐mediated apoptosis endows the hematopoietic progenitors themselves with a potent regulatory activity against the host alloreactive responses, as previously suggested [31, , 34]. The early timing of this veto activity preceded the eventual early evolution of donor‐derived myeloid cells with immune capacity [38, 39]. Thus, it is the hematopoietic precursors themselves that are involved in presentation of the donor antigens, primarily the major histocompatibility antigens in the fully allogeneic transplants [34].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The early immunomodulation achieved by expression of FasL protein on the surface of HSPC in concert with the insensitivity of these cells to Fas‐mediated apoptosis endows the hematopoietic progenitors themselves with a potent regulatory activity against the host alloreactive responses, as previously suggested [31, , 34]. The early timing of this veto activity preceded the eventual early evolution of donor‐derived myeloid cells with immune capacity [38, 39]. Thus, it is the hematopoietic precursors themselves that are involved in presentation of the donor antigens, primarily the major histocompatibility antigens in the fully allogeneic transplants [34].…”
Section: Discussionmentioning
confidence: 95%
“…The upregulation of Fas and FasL expression on bone marrow‐homed donor HSPC indicated that this molecular interaction is relevant to the very early stages of engraftment. Therefore, we used a FasL protein that has a very short lifetime in vivo [13, 37] and is diluted during the differentiation myeloid progenitors that may generate immunogenic activities [38, 39]. The protein aggregates spontaneously to deliver potent apoptotic signals through trimerization of the Fas receptor and also may be adhered to the surface of cells via biotinylation.…”
Section: Introductionmentioning
confidence: 99%
“…et al, unpublished data), perhaps donor T cells are responsible for the functional effect seen. Potential mechanisms include induction of anergy in recipient T cells by non-professional presentation of alloantigens by transferred donor T cells 24,25 ; limited graftversus-host effects, causing a suppression of the recipient's immune system 26 ; or 'veto' effects, which have been demonstrated in rodent 27 as well as monkey 28 and human systems 29 . However, these immunological effects of early postoperative microchimerism are different from those of stable mixed allogeneic (macro)chimerism, which is associated with stable donor-specific transplantation tolerance due to thymic, deletional mechanisms 30,31 .…”
Section: Discussionmentioning
confidence: 99%
“…in the presence of either cyclosporin or tacrolimus. Thus, several of the parameters present in the setting of clinical organ transplantation favour prolonged survival of the passenger cells and may thereby enable functional effects of passenger lymphocytes on the recipient's immune system [20–23]. To what extent two‐way interactions between allogeneic immunocompetent cells early after organ transplantation are also important for the development of long‐term microchimerism, a phenomenon frequently observed after solid organ transplantation, [24–26] remains speculative.…”
Section: Discussionmentioning
confidence: 99%